2010
DOI: 10.1124/dmd.110.035196
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin and Thioredoxin Can Be Involved in Producing the Pharmacologically Active Metabolite of a Thienopyridine Antiplatelet Agent, Prasugrel

Abstract: ABSTRACT:A thienopyridine antiplatelet agent, prasugrel, is rapidly hydrolyzed to a thiolactone metabolite (R-95913, 2-[2-oxo-6,7-dihydrothieno[3,2-c]pyridin-5(4H)-yl]-1-cyclopropyl-2-(2-fluorophenyl)ethanone). R-95913 is oxidized by hepatic cytochromes P450 to the pharmacologically active metabolite R-138727 (2-[1-2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4-mercapto-3-piperidinylidene]acetic acid). One possible intermediate in the in vitro bioactivation pathway is a glutathione conjugate, R-133490, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…In the absence of cytosol, the reduction of the CPT conjugate is approximately one-half as fast, with a rate constant of 0.39 minute 21 for the reduction of the conjugate and 0.35 minute 21 for the formation of the AM. This indicates that cytosol accelerates the reduction of the thiol-disulfide exchange reaction, as observed previously (Hagihara et al, 2011(Hagihara et al, , 2012. We confirmed this observation by use of boiled cytosol, as shown in Supplemental Fig.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In the absence of cytosol, the reduction of the CPT conjugate is approximately one-half as fast, with a rate constant of 0.39 minute 21 for the reduction of the conjugate and 0.35 minute 21 for the formation of the AM. This indicates that cytosol accelerates the reduction of the thiol-disulfide exchange reaction, as observed previously (Hagihara et al, 2011(Hagihara et al, , 2012. We confirmed this observation by use of boiled cytosol, as shown in Supplemental Fig.…”
supporting
confidence: 76%
“…In addition, it is shown that the thiol-disulfide exchange reactions are facilitated by the cytosolic fraction of human liver. This is likely due to the involvement of glutaredoxin and/or thioredoxin in the thiol-disulfide exchange reaction as previously reported (Hagihara et al, 2011(Hagihara et al, , 2012.…”
Section: Mixed Disulfide Conjugates Of Clopidogrelmentioning
confidence: 65%
“…Although the exact mechanism by which ClopNPT is converted to the active metabolite in vivo remains to be elucidated, it is likely that ClopNPT is converted to the active metabolite by a thiol disulfide exchange reaction with glutathione (Zhang et al, 2013). This exchange may also be accelerated by glutaredoxin and thioredoxin (Hagihara et al, 2011(Hagihara et al, , 2012. The rapid conversion of ClopNPT to the active metabolite also occurs after intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…This low level of active metabolite may be prone to changes as a result of factors other than P450-catalyzed reactions, such as the concentrations of GSH or other reductants that may be associated with oxidative stress or inflammation. In addition, a study by Hagihara et al (2011) demonstrated that glutaredoxin and thioredoxin accelerated the conversion of the glutathionyl conjugate of the active metabolite of prasugrel, another thienopyridine antiplatelet agent like clopidogrel, to the active metabolite. It is unclear to what extent glutaredoxin and thioredoxin may contribute to the metabolism of clopidogrel to its active metabolite.…”
Section: Discussionmentioning
confidence: 99%